Construction of Self-Identity of Baduy Muslim Residents on Social Media - Amrullah, Haekal Fajri; Bate, Andi Pajolloi; Sungkono, Nono; Mahmudi, Marwan (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
The phenomenon of religious conversion becomes interesting when the Baduy tribe, known as a tribe that holds fast to its customs and beliefs, converts or converts to Islam. The discussion of self-identity becomes even more unique and interesting when a Muslim Baduy citizen still uses the Baduy identity to show their identity, one of which is through social media. Social media functions as a means for users to place themselves in the framework they want, easily establish relationships, increase insight, form, express and display their identity. Identity is a picture of the cultural, social, relational, and individual self. The purpose of this study is to examine how Muslim Baduy citizens construct their identities on Instagram social media. This study uses a qualitative approach with a case study method. Through data collection techniques through interviews conducted with Muslim Baduy citizens who have used Instagram social media. The results of the study show that the self-identity shown by Muslim Baduy citizens on social media is generally like ordinary citizens. The Baduy identity that is attached to them cannot be easily removed, even though their lives are modern. The existence of social media is used to provide an explanation that they want to be known as Muslims only, no longer called Baduy Mualaf.